2010
DOI: 10.2460/ajvr.71.5.508
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical loading of the distal end of the third metacarpal bone in horses during walking and trotting

Abstract: Results of strain gauge and kinematic analyses indicated that the major structures of the distal portion of the forelimb in horses acted to load the distal end of the third metacarpal bone in axial compression throughout the stance phase of the stride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Several investigators have used simple models of the equine third metacarpal bone and shown good agreement with ex vivo results. 24,[32][33][34] These validation results support that the FE modelling approach had acceptable agreement with ex vivo testing.…”
Section: Discussionsupporting
confidence: 65%
“…Several investigators have used simple models of the equine third metacarpal bone and shown good agreement with ex vivo results. 24,[32][33][34] These validation results support that the FE modelling approach had acceptable agreement with ex vivo testing.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, a greater proportion (60%) of the body weight of the horse is borne on the front legs (Leach, ; Mcduffee et al., ). Additionally, the Mc3 in the stance phase is primarily loaded in axial compression (Merritt et al., ) and the distal part of the metacarpus is loaded asymmetrically resulting in more compressive strain on the medial aspect (Firth et al., ). Therefore, the significant variations in widths and depths between the medial and lateral condyles (the medial was the widest and deepest) in the individual bones could be an adaptation occurring in the distal Mc3 bones during development to receive that loading.…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed analysis of limb loading is achieved with computational modelling, which allows the calculation of loads in multiple structures and at multiple sites throughout the limb. Modelling of the equine forelimb has been used to calculate loads throughout the distal portion of the third metacarpal bone and at the joint surfaces . For a cantering horse (6.2 m/s) the largest loads (24 kN) occur at the carpal and fetlock joint surfaces .…”
Section: Relationship Between Magnitude Of Load and Fatigue Lifementioning
confidence: 99%